Early versus late initiation of infliximab for refractory uveitis in a cohort of Egyptian BD patients - Mariam R Fadel; Shereen H AboulNaga; Nehal ElGhobashy; Sally S. Mohamed (Journal of the Egyptian Ophthalmological Society)
Introduction Behçet’s syndrome is a multisystem inflammatory disease characterized by recurrent oral aphthous ulcers, genital ulcers, skin lesions, and uveitis. Ocular involvement, occurring roughly in 50% of patients, is one of the most feared complications of Behçet’s syndrome. Recurrent severe uveitis leads to irreversible severe vision loss.